Organizational commitment and organizational citizenship behaviour: a study among public sector employees - Ismail, Suriani; Mohd Ali, Siti Shazwani; Nazuri, Nur Shuhamin (RSIS International, 2024)
Organizational commitment reflects employees’ dedication to their organization, while organizational citizenship behavior (OCB) entails voluntary actions beyond formal job duties. Strong commitment fosters positive work environments and encourages behaviors benefiting the organization, like assisting colleagues or suggesting improvements. Research has primarily explored the relationship between overall organizational commitment and OCB, often overlooking the distinct impacts of its various dimensions. Furthermore, limited attention has been given to how affective, continuance and normative commitment uniquely contribute to the different aspects of OCB among public sector employees. On top of that, this paper discusses extensive findings and the theoretical basis explaining the relationship between organizational commitment and OCB, which was limited in the literature. This study addresses these gaps by reviewing Social Exchange Theory (SET) to explain the effect of organizational commitment on OCB and thoroughly examine the relationship between these variables. The findings of this study have practical implications that can empower organizations to enhance employee engagement and performance. They reveal that continuance and normative commitments significantly influence OCB, suggesting that organizations can strengthen these commitments by providing clear career paths, recognizing employee contributions, and fostering a strong sense of organizational loyalty.